Competitive factors affecting the expansion of Greenfield elevator sites - Wisner, Michael (Kansas State University, 2013)
The purpose of this thesis is to identify Greenfield grain facility sites within 100 miles of Holdrege, Nebraska and to evaluate the feasibility of these sites. CHS Agri Service Center currently has facilities that are within 50 miles of Holdrege, Nebraska. However there are no Greenfield sites in this area that would be feasible due to a large number of competitors already operating in this area. This problem was broken down into two components. The first is site selection and the second is a financial model using net present value to determine if the sites selected would be profitable to the standards that CHS, Inc. requires (12% or better return on assets). In order to determine where Greenfield sites might be located supply and demand factors were evaluated to determine surplus and deficit grain areas. The areas where there were large surpluses of grain have the greatest potential for a Greenfield facility to succeed. Then a feasibility analysis of the chosen sites is conducted using net present value and internal rate of return analysis to determine if there is enough grain volume to operate the grain facility above the 12% return on assets criterion. After a detailed review of the supply and demand factors of grain in the region, two locations were determined to be good candidates for further study. Based on recent projects completed at CHS, Inc. two model facilities were created as tools to determine if a certain facility type is more profitable than another. The cost structures for these two model facilities are based on costs that are currently incurred at CHS Agri Service Center locations. It was found that neither facility at either location was profitable enough to meet the minimum performance criteria required by CHS, Inc. As a result of these findings it may be possible to move ahead with a Greenfield facility at one of these sites if a higher volume can be obtained. A merger with another grain company in the immediate area of the proposed facility may be the best way to increase volume.
Keywords: Grain marketing; Logistics; Greenfield locations; Agriculture, General (0473); Economics (0501); Economics, Commerce-Business (0505)